The Solutions of Writing Undergraduate Thesis: A Narrative Inquiry Case Study - Endah Yulia Rahayu; Moesarofah Moesarofah (Linguistics and ELT Journal, 2022)
EFL undergraduates have been making every effort to finish their theses throughout the process of thesis proposal, thesis proposal exam, writing thesis, oral thesis test, and thesis revision. This study invited four graduates of the English department who had finished their thesis within six months or less. They were interviewed in-depth via Zoom to reveal the tactics and solutions they had used to succeed in their undergraduate thesis. The authors used a narrative inquiry case study to justify their experiences, solutions, and strategies in writing their thesis. The participants understood the difficulty of conducting research and writing a thesis but overcame it through perseverance, determination, and self-discipline. They did various research preparation tasks during the thesis proposal, such as reading related sources to strengthen their references and learning how to create a thesis. They lacked the confidence to attend the thesis proposal exam, but they prepared it at their best. They could complete each section of the thesis with the help of their peers and advisor. Maintaining positive relationships with one's mentor, examiner, and peers could help them feel more confident in their writing and reduce the stress associated with writing a thesis. They calmed their tension, reread all thesis chapters, and practiced their presentation to ace their thesis examination. They were able to complete their thesis revision on schedule due to the guidance of their thesis mentor and an encouraging examiner. How further research solutions of the four participants were elucidated in this study.